Susceptibilidad antimicrobiana de Pseudomonas aeruginosa aislada de visones enfermos - Pantozzi, Florencia L. (2000)
Bacterial susceptibility of 40 isolates of Pseudomonas aeruginosa to six antimicrobial agents ceftiofur (CFT), colistin (COL), danofloxacin (DNF), enrofloxacin (ENF), gentamicin (GEN), and trimethoprim:sulphamethoxazole (TMS) (ratio 1:19) were determined for the minimal inhibitory concentration (MIC) using the agar-dilution method. All strains were from ranch-raised mink (Mustela vison) origin, were considered clinically important (mostly with Pneumonia infection) and were collected during the past fourteen years. The MIC that prevented the growth of 90 % of the bacteria were in mg/ml, 100 for CFT, 100 for COL, 1.57 for DNF and ENF, 12.5 for GEN and > 100 for TMS. The fluoroquinolones showed higher activity in our strains than the classical antibiotics used against Pseudomonas aeruginosa. Based on the MIC values obtained and taking into account the administration form (mixed into the feed or water supply) of these drugs, we consider that they might be useful for treatment on this illness.